Massive intrathoracic lipoma in men1 syndrome. (2015) - Sturiale, Alessandro; Giudici, Francesco; Alemanno, Giovanni; Cavalli, Tiziana; Addasi, Rami; Santomaggio, Carmine; Meoni, Giulia; Brandi, Maria Luisa; Tonelli, Francesco
Abstract: Introduction: The multiple endocrine neoplasia type 1 (MEN1) is a rare autosomal dominant syndrome characterized by the onset of hyperparathyroidism, gastroenteropancreatic neuroendocrine tumors and pituitary lesions. Presentation of case: This appears to be the first described case of a massive intrathoracic lipoma in MEN1. The patient was affected with primary hyperparathyroidism treated with a total parathyroidectomy followed by a distal pancreatectomy for insulinoma. At follow-up, the computed tomography showed a massive lesion on the left emithorax suggestive of a lipoma. At the onset of a mild dyspnea we decided to perform the surgical excision of the mass obtaining a complete relief of the symptoms. Discussion: This case is evidence of the importance of a strict follow-up of such patients. Conclusion: Lipomas are the most frequent benign soft tissue tumors. They are usually sporadic but are sometimes related to hereditary syndromes. Intrathoracic localizations are rare and can arise mainly in the mediastinum, bronchus or lung. The diagnosis is often incidental; despite preoperative imaging will accurately show the features of the lesions, it is impossible obtain an accurate diagnosis-hence, the treatment of choice remains the surgical excision.